EVALUASI KEBIJAKAN WORK FROM HOME BAGI APARATUR SIPIL NEGERI PADA MASA PANDEMI COVID-19 DI BADAN PERENCANAAN PEMBANGUNAN DAERAH KOTA PEKANBARU TAHUN 2021 - Linda Yusnita Siregar; Rury Febrina (Kemudi, 2022)
The implementation of the WFH policy during the Covid-19 pandemic certainly has responsibilities and obligations that are no different from working in an office. However, it can be seen from the fact that in its implementation, WFH cannot be separated from challenges and obstacles that must be faced, this is because not all work can be carried out from home. This study aims to evaluate the implementation of the WFH policy in the Pekanbaru City BAPPEDA work environment during the Covid-19 pandemic. This research uses descriptive qualitative method. The data obtained were sourced from the head of the personnel department at BAPPEDA Pekanbaru City. Data collection was carried out through observation, interviews, and collecting documents supporting the research. The results obtained indicate that based on evaluation activities by paying attention to the 6 (six) evaluation criteria such as effectiveness, efficiency, adequacy, leveling, responsiveness, and accuracy that have been carried out and can be seen where in practice, with the existence of WFH that has not been able to run properly. good and there is a tendency that there is a decline in public services. It can be seen that, there are obstacles from the existence of WFH which include aspects of computer availability, aspects of the ability to master information technology, and aspects of performance appraisal.